Plain language summary of isatuximab plus carfilzomib, lenalidomide, and dexamethasone for the treatment of people with high-risk newly diagnosed multiple myeloma - Leypoldt, Lisa; Tichy, Diana; Besemer, Britta; Hanel, Mathias; Raab, Marc-Steffen; Mann, Christoph; Munder, Markus; Reinhardt, Hans Christian; Nogai, Axel; Gorner, Martin; Ko, Yon-Dschun; Wit, Maike de; et al. (Future oncology, 2024)
This is a summary of a publication about the GMMG-CONCEPT study that was published in the Journal of Clinical Oncology in September 2023. The study tested if a combination of cancer drugs (isatuximab plus carfilzomib, lenalidomide, and dexamethasone, or Isa-KRd for short) was a safe treatment for people with highrisk newly diagnosed multiple myeloma. The GMMG-CONCEPT study included participants who had not been treated before and were eligible to receive a procedure called autologous stem cell transplant, as well as participants who were not eligible to receive transplants. This report looked at a total of 125 participants; 99 were transplant-eligible and 26 were transplant-non-eligible. All participants were treated with Isa-KRd. The researchers measured the proportion of people who had ‘no detectable levels’ of myeloma cells in their body left while on treatment (called minimal residual disease negativity, or MRD negativity for short). The researchers measured the progression-free survival, or the average length of time it took between the participants joining the study until their cancer got worse or they died. The researchers also measured overall survival, which is the total amount of time people lived during the study, even if their cancer got worse. The researchers also monitored for side effects of Isa-KRd in all participants that received at least one treatment. At the end of the consolidation therapy (intensified therapy that happens after initial therapy), MRD negativity was observed in the majority of transplant-eligible and transplant non-eligible patients. For many patients, this effect lasted 6 or more months. After more than 3 years in transplant eligible participants and 2 years and 9 months for transplant non-eligible participants, most participants were alive and their disease did not get worse. In both groups, the most common side effects of Isa-KRd treatment were low blood cell counts and infections. Overall, most of the side effects did not last long or were easily treated. In the GMMG-CONCEPT study, Isa-KRd treatment reduced the number of myeloma cells to no detectable levels in more than two thirds of the participants with high-risk newly diagnosed multiple myeloma. Clinical Trial Registration: NCT03104842 (ClinicalTrials.gov)